LEGISLATION (INDIA TRADEMARK LAW) - BHANDARI, S. S.; KABRA, M. P.; KUMAR, H.; SINGH, SANDEEP; NEGI, KAPIL (Asian Journal of Pharmaceutical Research and Development, 2013)
A trade mark is a visual symbol that distinguishes the goods or services of one enterprise from those of the competitors. A reference to goods will imply services also, unless the context prohibits it. Trade Marks are at the centre of global business today. They are the major source of product differentiation and non-price competition in a modern, market driven economy. Consumers come to associate certain value in terms of performance, durability, price, after-sales service etc in the goods sold under specific brands, which may be among the greatest assets of the enterprise. In the language of the law, brand names are known as trademarks. Several products, of the same category or of different categories, can be marketed under one brand name. Recently, non-visual signs have made a strong claim for recognition as trademarks. Smell and sound signs fall under such category though they are not yet recognised in India. Several broadcasting organisations and film producers have specific signature tunes to identify their programmes. This article review about the features of legislation, function and selection of trademark, types of trademark that can be registered, duration and benefits of trademark, who can apply and use the trademark, how to apply for and formalities of major trademark transaction.